(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study evaluated the effect of access to facial expressions on explanations of clicking behavior in mixed (unsignaled) and multiple (signaled) reinforcement schedules, composed of DRL 10 s and VR 4. Twenty adults were instructed to explain, in writing, the clicking behavior of two individuals in four videos. Half of the participants had access to the individuals’ facial expressions. Explanations were classified into (a) reference to public events observable in the video; (b) reference to hypothetical public events; and (c) reference to private events. The results suggest that access to the expressions and to the mixed schedule evoke internalist explanations and have subtle effects on other explanatory classifications. In conditions in which it is important to teach individuals to explain behaviors and act on them, strategies that allow access to clearly discriminable situations and to the history producing current behaviors can be considered.